2019
DOI: 10.1016/j.talanta.2019.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide arrays for wide spectrum sensing of pathogenic bacteria

Abstract: Fast detection of bacteria in samples presumed to be un-contaminated, such as blood, is of great importance. Indeed, rapid diagnosis allows the setup of appropriate antibiotic treatment. Besides clinical issues, there are many other domains, such as food processing or drug manufacturing, where the strict absence of any bacteria has to be assessed. Because the bacterial load found in most contaminated samples is often below the limit of detection for currently validated assays, a preliminary enrichment step is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…as models for Gram-negative and Gram-positive bacteria, respectively. The screening potential of our system can be improved by analyzing bacterial motility patterns by using a larger set of AMPs with complementary affinity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as models for Gram-negative and Gram-positive bacteria, respectively. The screening potential of our system can be improved by analyzing bacterial motility patterns by using a larger set of AMPs with complementary affinity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, pHEMA-AEM (2-hydroxyethylmethacrylate (HEMA) 2-Aminoethyl methacrylate hydrochloride (AEM)) is a polymeric cryogel synthesized through a cryostructuration method characterized by a large inner surface area, resulting in a high capacity for bacteria harvesting, even from complex samples [ 14 ]. Antimicrobial peptides (AMPs) bioreceptors were shown to be an interesting alternative to antibodies due to their broad recognition spectrum [ 15 , 16 , 17 ]. AMPs are a subset of peptides presenting strong bactericidal activity against Gram-positive and Gram-negative bacteria according to specific patterns [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the electrochemical assay designed by Wilson et al [72] has similar features compared to other electrochemical biosensors operating in food [96]. Alternatively, some systems based on AMPs such as the SPR imaging device we designed [85] do not present faster detection times than previous studies [86][87][88]. However, it is able to detect a broader range of bacteria than devices based on antibodies.…”
Section: Perspectives and Outlookmentioning
confidence: 96%
“…In a recent study [85], we proposed an approach inspired from a strategy proven to be able to detect pathogens at low concentrations, even in complex matrices [86][87][88]. This assay, based on surface plasmon resonance (SPR) imaging enables the monitoring of growing pathogens, thanks to the "Culture-Capture-Measure" method.…”
Section: Biosensors Based Solely On Amps For the Recognition Of Bacteriamentioning
confidence: 99%
“…Recently, AMPs have been used as ligands in biosensors to detect whole-cell bacteria because of their broad-spectrum specificity [14,15]. A microarray chip coupled with multiple AMPs was designed for surface plasmon resonance imaging (SPRI) by Pardoux et al, in which pathogens can be detected using this multiplexing AMP array within 20 h [16]. Kim et al reported a two-stage label-free aptasensing platform for the detection of Cronobacter sakazakii in powdered infant formula [17].…”
Section: Introductionmentioning
confidence: 99%